Identity of the ‘true’ Micraspis discolor (Fabricius) (Coleoptera, Coccinellidae) with illustrated diagnostic notes on other Micraspis spp. in Indian paddy fields - Poorani, J.; Booth, Roger G.; Anuradha, C.; Gracy, R. Gandhi; Thanigairaj, R.; Swathi, R. S. (Zootaxa, 2023)
Micraspis discolor (Fabricius, 1798) (Coleoptera: Coccinellidae), a widely studied complex of externally similar species, is known to be distributed in all the major rice growing countries of the Oriental region. It consists of disjunct populations that have been treated as a single taxonomic entity, but these are not conspecific and show disparities in their morphology. In this paper, we establish the identity of the true M. discolor based on Fabricius’s type material from Tamil Nadu, Southern India, and redescribe it with illustrations of the diagnostic characters and the life stages. A lectotype is designated for M. discolor from Fabricius’s type material (lectotype designation). Coccinella tenuilinea Walker, 1859, a sympatric species closely related to M. discolor and omitted from Korschefsky’s World Catalogue of Coccinellidae, is transferred to Micraspis (new combination) and a lectotype is designated for it. It is found to be the most predominant species in South India and redescribed with illustrations of the genitalia and the life stages. COI sequences of M. discolor, M. tenuilinea and M. yasumatsui Sasaji based on the material collected in India are given. Phylogenetic analysis of the COI sequences of Indian M. discolor and other Asian ‘M. discolor’ sequences confirm that the Indian M. discolor is a distinct species and all Micraspis spp. from South and southeast Asian countries not matching the true M. discolor described here need to be re-examined and renamed if necessary. Brief illustrated accounts of other Micraspis spp. known from the paddy ecosystems of India are also given. Alesia guerini Mulsant, 1850, currently placed in Micraspis, is transferred to Oenopia Mulsant (new combination) and Coelophora walteri Sicard, 1913 is a new junior synonym of O. guerini (new synonym).